Composite coating diaphragm for lithium ion battery and preparation method of composite coating diaphragm
By using a composite coating process of cross-linked structure aramid polymer and TiO2 sol on the lithium-ion battery separator, the problems of poor heat resistance and uneven coating at high temperatures are solved, and higher heat resistance and The puncture strength improves the electrochemical and safety performance of the battery.
Patent Information
- Application Number
- CN202411783055.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing lithium-ion battery separators have poor heat resistance, uneven coating and insufficient composite force at high temperatures, resulting in the problem of easy coating falling off.
The composite coating process of cross-linked structure aramid polymer solution and TiO2 sol is adopted. By coating the TiO2 treatment solution multiple times on the surface of the intermediate of the aramid coating membrane, a uniform porous structure is formed and the adhesion of the coating is improved.
It significantly improves the heat resistance, puncture strength and low water absorption properties of the diaphragm, enhances electrochemical and safety performance, and ensures the stability and safety of the battery under high temperature conditions.
Smart Images

Figure CN119253192A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite coating diaphragm for lithium ion batteries and a preparation method thereof, belonging to the technical field of battery diaphragms. Background Art
[0002] Lithium-ion battery separators are electrically insulating films with a porous structure. As an important component of lithium batteries, their main function is to block the positive and negative plates to prevent short circuits inside the battery. The separators have nanoscale pores to allow lithium ions to be quickly transferred between the positive and negative electrodes during electrochemical charge and discharge, and are an important determinant of battery capacity, cycle capacity, and safety performance.
[0003] As applications become increasingly widespread and in-depth, the market demand for lithium-ion batteries is developing towards high capacity, fast charging and discharging, long battery life and a wide temperature range. However, high-intensity continuous operation may cause the battery to be in a high temperature state for a long time, so the market has put forward higher requirements on its temperature resistance.
[0004] In recent years, aramid coated diaphragms have become a new type of lithium battery diaphragm solution, and many diaphragm manufacturers have placed their hopes on aramid materials for high temperature resistant coated diaphragms. Chinese patent application CN110444714A provides a ceramic aramid coated diaphragm for lithium ion batteries and a preparation method thereof. Limited by the aramid material itself, the 150°C temperature resistance (heat shrinkage rate) only reaches 10%, which cannot meet the temperature resistance performance at higher temperatures. Other aramid coated diaphragms have not reached a higher level of temperature resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a composite coated diaphragm for lithium ion batteries and a preparation method thereof, which solves the problems of poor heat shrinkage of the coated diaphragm (the diaphragm shrinks and deforms severely at a high temperature of 180°C), uneven coating, insufficient composite force between coatings, and easy shedding of the coating.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a composite coated diaphragm for a lithium ion battery, the preparation method comprising: S1. Preparation of aramid coated diaphragm intermediate: Aramid polymer slurry is coated on the base film, and subjected to coagulation bath molding and drying treatment to obtain an aramid coated diaphragm intermediate; the aramid polymer slurry comprises a cross-linked aramid polymer solution, a porogen and a cosolvent; The cross-linked aramid polymer solution is prepared by cross-linking a meta-aramid polymer solution and an isocyanate inducing agent, and the weight average molecular weight of the cross-linked aramid polymer in the cross-linked aramid polymer solution is 15-30W; S2. Preparation of composite coated diaphragm: A TiO2 treatment liquid is coated on the surface of the aramid coated diaphragm intermediate, and finally a drying treatment is performed to obtain a composite coated diaphragm; the TiO2 treatment liquid includes a TiO2 sol and an aqueous adhesive.
[0007] Furthermore, the cross-linked structure polymer in the cross-linked structure aramid polymer solution is selected from the following chemical formula: , ; R is selected from any one of the following structures: ; 0≤n≤150, 80≤x≤150, 80≤m≤150.
[0008] Furthermore, the porogen is any one of polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; The co-solvent is any one of calcium chloride and lithium chloride; The isocyanate inducer is at least one of 2,4- / 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, naphthalene 1,5-diisocyanate, p-phenylene diisocyanate, and triphenylmethane triisocyanate.
[0009] Furthermore, in step S1, the mass ratio of the cross-linked aramid polymer solution to the porogen and the cosolvent is (80-89): (5-8): (6-12); The solid content of the cross-linked aramid polymer solution is 5%-15%.
[0010] Furthermore, in step S1, the coagulation bath is a DMAC aqueous solution with a mass concentration of 20-65%; and the coagulation bath temperature is 10-40°C.
[0011] Further, in step S2, the preparation method of TiO2 sol is: (1) Add tetrabutyl titanate and acid to alcohol and stir and mix, control the temperature to 10-45° C., the stirring speed to 300-800 rpm, and the stirring time to 1-3 h to obtain a mixed solution A; (2) After the alcohol and water are evenly mixed, slowly add them into the mixed solution A and stir to mix. Control the temperature to 10-45°C, the stirring speed to 500-1500 rpm, and the stirring time to 2-4 hours to obtain TiO2 sol.
[0012] Further, the mass ratio of tetrabutyl titanate to acid is 1:(0.5-3); The mass ratio of the total mass of the alcohol in step (1) and step (2) to the mass ratio of the tetrabutyl titanate is (2-5):1; The mass ratio of water to tetrabutyl titanate is (0.5-3):3; The mass ratio of the alcohol in step (1) to the alcohol in step (2) is (1.8-2.2): 1; The alcohol is any one of methanol, ethanol, isopropanol and n-butanol; The acid is any one of acetic acid, nitric acid and phosphoric acid.
[0013] Furthermore, the water-based adhesive is at least one of polypropylene resin, polyacrylic acid, polyvinyl alcohol, polyacrylonitrile, and poly(meth)acrylate; The mass proportion of the aqueous adhesive in the TiO2 treatment solution is 1-10%.
[0014] Furthermore, in step S2, the method for coating the TiO2 treatment liquid on the surface of the aramid coated diaphragm intermediate is: immersing the aramid coated diaphragm intermediate in the TiO2 treatment liquid for multiple times, controlling the immersion penetration speed to 20-80m / min, the immersion penetration number to 2-5 times, and finally drying and processing to obtain a composite coated diaphragm.
[0015] A composite coated diaphragm for lithium ion batteries, wherein the composite coated diaphragm is prepared according to the preparation method of the present invention.
[0016] The beneficial effects of the present invention are: The invention discloses a composite coated diaphragm for a lithium ion battery and a preparation method thereof. The cross-linked structure polymer and TiO2 sol inorganic material coating layer used in the preparation process have better uniformity and low water absorption characteristics, so that the prepared composite coated diaphragm has higher heat resistance, film rupture temperature, puncture strength and low water absorption performance; in addition, due to the larger coating pore structure after the aramid polymer is formed into a film and the unique chemical structure of the amide bond, the manufactured product has more excellent liquid retention performance, and exhibits better electrochemical and safety performance after the battery is assembled.
[0017] In the preparation method of the present invention, by controlling the coating process conditions of each layer, it is more conducive to obtaining a composite coated diaphragm with a suitable pore structure, so that the composite coated diaphragm has good air permeability and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a flow chart of the preparation method of the aramid coated diaphragm intermediate of the present invention; Figure 2 is a flow chart of the preparation method of the composite coated diaphragm described in Example 1; Figure 3 is a surface morphology image of the composite coated diaphragm in Example 1; Figure 4 This is a test diagram of the film rupture temperature of the composite coated diaphragm in Example 1. DETAILED DESCRIPTION
[0019] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0021] A method for preparing a composite coated diaphragm for a lithium ion battery, the preparation method comprising: S1. Preparation of aramid coated diaphragm intermediate: Aramid polymer slurry is coated on the base membrane, and a uniform porous structure is formed by coagulation bath molding to construct a stable porous coating structure, and then an aramid coated diaphragm intermediate is obtained by drying. The aramid polymer slurry comprises a cross-linked aramid polymer solution, a porogen and a cosolvent; The cross-linked aramid polymer solution is prepared by cross-linking a meta-aramid polymer solution and an isocyanate inducing agent, and the weight average molecular weight of the cross-linked aramid polymer in the cross-linked aramid polymer solution is 15-30W; the process flow is as follows: Figure 1 shown.
[0022] S2. Preparation of composite coated diaphragm: A TiO2 treatment liquid is coated on the surface of the aramid coated diaphragm intermediate, and finally dried to obtain a composite coated diaphragm; the TiO2 treatment liquid includes TiO2 sol and water-based adhesive. Figure 2 shown.
[0023] Specifically, the cross-linked structure polymer in the cross-linked structure aramid polymer solution is selected from the following chemical formula: , ; R is selected from any one of the following structures: ; 0≤n≤150, 80≤x≤150, 80≤m≤150; such cross-linked structured materials have better temperature resistance and higher strength.
[0024] Specifically, the porogen is any one of polyethylene glycol (PEG), polyvinyl alcohol (PVA), and polyvinyl pyrrolidone (PVP); The co-solvent is any one of calcium chloride and lithium chloride; The isocyanate inducer is at least one of 2,4- / 2,6-toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), and triphenylmethane triisocyanate (PMDI).
[0025] More specifically, the preparation method of the cross-linked aramid polymer solution is as follows: dissolving the meta-aramid polymer stock solution in DMAC, controlling the system temperature to 25-35° C., slowly adding an isocyanate inducing agent for reaction, controlling the reaction time to 10-15 min, and obtaining the cross-linked aramid polymer solution after the reaction is completed.
[0026] Specifically, the solvent in the meta-aramid polymer stock solution is DMAC, the polymer mass percentage is 11-35%, and the viscosity (25° C.) is 80000-120000 mPa·s.
[0027] More specifically, in order to better reflect the influence of various process conditions on the product, the same meta-aramid polymer stock solution is used in each embodiment and comparative example of the present invention, and the solvent in the meta-aramid polymer stock solution used in each embodiment and comparative example of the present invention is DMAC, the polymer mass percentage is 20%, and the viscosity (25°C) is 100000 mPa·s. However, this is not a limitation to the technical solution of the present invention.
[0028] Specifically, in step S1, the mass ratio of the cross-linked aramid polymer solution to the porogen and the cosolvent is (80-89): (5-8): (6-12); The solid content of the cross-linked aramid polymer solution is 5%-15%.
[0029] More specifically, when preparing the aramid coated diaphragm intermediate in step S1, the aramid polymer slurry is coated on one side or both sides of the base membrane.
[0030] Specifically, in step S1, the coagulation bath is a DMAC aqueous solution with a mass concentration of 20-65%; the coagulation bath temperature is 10-40°C.
[0031] Specifically, in step S2, the precursor tetrabutyl titanate is firstly hydrolyzed under suitable conditions by a sol-gel method to obtain a transparent TiO2 sol. The specific preparation process is as follows: (1) Add tetrabutyl titanate and acid to alcohol and stir and mix, control the temperature to 10-45° C., the stirring speed to 300-800 rpm, and the stirring time to 1-3 h to obtain a mixed solution A; (2) After the alcohol and water are evenly mixed, slowly add them into the mixed solution A and stir to mix. Control the temperature to 10-45°C, the stirring speed to 500-1500 rpm, and the stirring time to 2-4 hours to obtain TiO2 sol.
[0032] Specifically, the mass ratio of tetrabutyl titanate to acid is 1:(0.5-3); The mass ratio of the total mass of the alcohol in step (1) and step (2) to the mass ratio of the tetrabutyl titanate is (2-5):1; The mass ratio of water to tetrabutyl titanate is (0.5-3):3; The mass ratio of the alcohol in step (1) to the alcohol in step (2) is (1.8-2.2):1.
[0033] The alcohol is any one of methanol, ethanol, isopropanol and n-butanol; The acid is any one of acetic acid, nitric acid and phosphoric acid.
[0034] Specifically, the water-based adhesive is at least one of polypropylene resin (CAS No.: 9003-07-0, ExxonMobil Corporation), polyacrylic acid (CAS No.: 9003-21-8, Shandong Xiya Chemical Co., Ltd.), polyvinyl alcohol (CAS No.: 96734-39-3, Jiangsu Runfeng Synthetic Technology Co., Ltd.), polyacrylonitrile (CAS No.: 25014-41-9, Jiangsu Leien Environmental Protection Technology Co., Ltd.), and poly (meth) acrylate (CAS No.: 9003-63-8, Jiangsu Bosite Chemical Technology Co., Ltd.); The mass proportion of the aqueous adhesive in the TiO2 treatment solution is 1-10%.
[0035] Specifically, in step S2, the method for coating the TiO2 treatment liquid on the surface of the aramid coated diaphragm intermediate is: immersing the aramid coated diaphragm intermediate in the TiO2 treatment liquid for multiple times, controlling the immersion speed to 20-80m / min, and the number of immersions to 2-10 times, to adjust the coating thickness and uniformity, and finally drying and processing to obtain a composite coated diaphragm.
[0036] More specifically, the base film is any one of a polyethylene film, a polypropylene film, a polypropylene / polyethylene / polypropylene three-layer composite microporous membrane, a polypropylene / polyethylene / polypropylene three-layer composite microporous membrane, a polyvinylidene fluoride microporous membrane, a polyvinylidene fluoride-hexafluoropropylene microporous membrane, a polyimide microporous membrane, a polyethylene non-woven fabric, a polypropylene non-woven fabric, a polyester non-woven fabric, and a polyimide non-woven fabric.
[0037] A composite coated diaphragm for lithium ion batteries, wherein the composite coated diaphragm is prepared according to the preparation method of the present invention.
[0038] Example 1 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0039] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 89:5:6 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5 μm on both sides was obtained.
[0040] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of anhydrous ethanol, add tetrabutyl titanate and acetic acid, the mass ratio of tetrabutyl titanate to acetic acid is 1:1, stir at 30°C and 500 rpm for 1.5 h to obtain a mixed solution A.
[0041] (2) Mix anhydrous ethanol and water evenly, slowly add them into mixed solution A, and stir at 30°C and 500 rpm for 3 h to obtain TiO2 sol; The mass ratio of anhydrous ethanol to tetrabutyl titanate in the TiO2 sol system is 3:1, and the mass ratio of water to tetrabutyl titanate is 1:3. The mass ratio of anhydrous ethanol in step (1) to anhydrous ethanol in step (2) is 2:1.
[0042] (3) Adding poly(meth)acrylate to the TiO2 sol, stirring at 30°C and 1000 rpm for 30 min, to obtain a TiO2 treatment solution, wherein the mass proportion of poly(meth)acrylate in the TiO2 treatment solution is 5%.
[0043] The aramid coated diaphragm intermediate obtained in step S1 is immersed in the TiO2 treatment solution at a speed of 50 m / min, and then placed in an oven for drying at 60°C. After drying, it is immersed in the TiO2 treatment solution again and dried at 60°C, and this is repeated 3 times. A composite coated diaphragm is obtained. The process flow is as follows: Figure 2 shown.
[0044] Example 2 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of NDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0045] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 89:5:6 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5 μm on both sides was obtained.
[0046] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of anhydrous ethanol, add tetrabutyl titanate and acetic acid, the mass ratio of tetrabutyl titanate to acetic acid is 1:1, stir at 30°C and 500 rpm for 1.5 h to obtain a mixed solution A.
[0047] (2) Mix anhydrous ethanol and water evenly, slowly add them into mixed solution A, and stir at 30°C and 500 rpm for 3 h to obtain TiO2 sol.
[0048] The mass ratio of anhydrous ethanol to tetrabutyl titanate in the TiO2 sol system is 3:1, and the mass ratio of water to tetrabutyl titanate is 1:3. The mass ratio of the alcohol in step (1) to the anhydrous ethanol in step (2) is 2:1.
[0049] (3) Adding poly(meth)acrylate to the TiO2 sol, stirring at 30°C and 1000 rpm for 30 min, to obtain a TiO2 treatment solution, wherein the mass proportion of poly(meth)acrylate in the TiO2 treatment solution is 5%.
[0050] The aramid coated diaphragm intermediate obtained in step S1 was immersed in the TiO2 treatment solution at a speed of 50 m / min, then placed in an oven for drying at 60° C., immersed in the TiO2 treatment solution again after drying, and dried at 60° C., and repeated for 3 times to obtain a composite coated diaphragm.
[0051] Example 3 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 15 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0052] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 80:8:12 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5 μm on both sides was obtained.
[0053] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of anhydrous ethanol, add tetrabutyl titanate and acetic acid to 2 / 3 of the amount, with the mass ratio of tetrabutyl titanate to acetic acid being 1:1, and stir at 30°C and 500 rpm for 1.5 h to obtain a mixed solution A.
[0054] (2) Mix anhydrous ethanol and water evenly, slowly add them into mixed solution A, and stir at 30°C and 500 rpm for 3 h to obtain TiO2 sol.
[0055] The mass ratio of anhydrous ethanol to tetrabutyl titanate in the TiO2 sol system is 3:1, and the mass ratio of water to tetrabutyl titanate is 1:3. The mass ratio of anhydrous ethanol in step (1) to anhydrous ethanol in step (2) is 2:1.
[0056] (3) Adding poly(meth)acrylate to the TiO2 sol, stirring at 30°C and 1000 rpm for 30 min, to obtain a TiO2 treatment solution, wherein the mass proportion of poly(meth)acrylate in the TiO2 treatment solution is 5%.
[0057] The aramid coated diaphragm intermediate obtained in step S1 was immersed in the TiO2 treatment solution at a speed of 50 m / min, then placed in an oven for drying at 60° C., immersed in the TiO2 treatment solution again after drying, and dried at 60° C., and repeated for 3 times to obtain a composite coated diaphragm.
[0058] Example 4 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0059] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 89:5:6 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5 μm on both sides was obtained.
[0060] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of anhydrous ethanol, add tetrabutyl titanate and nitric acid, the mass ratio of tetrabutyl titanate to acrylic acid is 1:1, and stir at 30°C and 500 rpm for 1.5 h to obtain a mixed solution A.
[0061] (2) Mix anhydrous ethanol and water evenly, slowly add them into mixed solution A, and stir at 30°C and 1000 rpm for 3 h to obtain TiO2 sol.
[0062] The mass ratio of anhydrous ethanol to tetrabutyl titanate in the TiO2 sol system is 3:1, and the mass ratio of water to tetrabutyl titanate is 1:3. The mass ratio of anhydrous ethanol in step (1) to anhydrous ethanol in step (2) is 2:1.
[0063] (3) Adding poly(meth)acrylate to the TiO2 sol, stirring at 30°C and 1000 rpm for 30 min, to obtain a TiO2 treatment solution, wherein the mass proportion of poly(meth)acrylate in the TiO2 treatment solution is 5%.
[0064] The aramid coated diaphragm intermediate obtained in step S1 was immersed in the TiO2 treatment solution at a speed of 50 m / min, then placed in an oven for drying at 60° C., immersed in the TiO2 treatment solution again after drying, and dried at 60° C., and repeated for 3 times to obtain a composite coated diaphragm.
[0065] Example 5 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0066] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 89:5:6 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5 μm on both sides was obtained.
[0067] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of anhydrous ethanol, add tetrabutyl titanate and acetic acid, the mass ratio of tetrabutyl titanate to acrylic acid is 1:1, and stir at 30°C and 500 rpm for 1.5 h to obtain a mixed solution A.
[0068] (2) Mix anhydrous ethanol and water evenly, slowly add them into mixed solution A, and stir at 30°C and 1000 rpm for 3 h to obtain TiO2 sol.
[0069] The mass ratio of anhydrous ethanol to tetrabutyl titanate in the TiO2 sol system is 3:1, and the mass ratio of water to tetrabutyl titanate is 1:3. The mass ratio of anhydrous ethanol in step (1) to anhydrous ethanol in step (2) is 2:1.
[0070] (3) Adding poly(meth)acrylate to the TiO2 sol, stirring at 30°C and 1000 rpm for 30 min, to obtain a TiO2 treatment solution, wherein the mass proportion of poly(meth)acrylate in the TiO2 treatment solution is 5%.
[0071] The aramid coated diaphragm intermediate obtained in step S1 is immersed in the TiO2 treatment solution at a speed of 50 m / min, and repeated twice, and then placed in an oven for drying at 60° C. to obtain a composite coated diaphragm.
[0072] Example 6 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of PPDI was slowly added. The processing time was 15 min to obtain a cross-linked aramid polymer solution.
[0073] The cross-linked aramid polymer solution, polyvinyl alcohol PVA (molecular weight 8000), and calcium chloride are mixed in a mass ratio of 85:6:9 to prepare an aramid polymer slurry, and then the aramid polymer slurry is evenly coated on a polyethylene diaphragm with a thickness of 7μm by micro-gravure coating, and then enters a coagulation bath (the coagulation bath is a solution of water and DMAC), the coagulation bath concentration is 20%, and the temperature is 10°C. After coming out of the coagulation bath, it is washed with water at 55°C, and then the diaphragm is dried at a drying temperature of 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5μm on both sides is obtained.
[0074] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of methanol, add tetrabutyl titanate and nitric acid, the mass ratio of tetrabutyl titanate to nitric acid is 1:0.5, stir at 45°C and 300 rpm for 1 h to obtain a mixed solution A.
[0075] (2) Mix methanol and water evenly, slowly add them into mixed solution A, and stir at 45°C and 1000 rpm for 2 h to obtain TiO2 sol; The mass ratio of methanol to tetrabutyl titanate in the TiO2 sol system is 2:1, and the mass ratio of water to tetrabutyl titanate is 0.5:3. The mass ratio of methanol in step (1) to methanol in step (2) is 2.2:1.
[0076] (3) Add polyacrylic acid to the TiO2 sol and stir at 30°C and 1000 rpm for 30 min to obtain a TiO2 treatment solution, in which the mass proportion of polyacrylic acid in the TiO2 treatment solution is 1%.
[0077] The aramid coated diaphragm intermediate obtained in step S1 was immersed in the TiO2 treatment solution at a speed of 20 m / min, then placed in an oven for drying at 60° C., immersed in the TiO2 treatment solution again after drying, and dried at 60° C., and repeated twice to obtain a composite coated diaphragm.
[0078] Example 7 S1. Preparation of aramid coated diaphragm intermediate: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of PMDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0079] The cross-linked aramid polymer solution, polyvinyl pyrrolidone (molecular weight 6000), and lithium chloride are mixed in a mass ratio of 82:8:10 to prepare an aramid polymer slurry, and then the aramid polymer slurry is evenly coated on a polyethylene diaphragm with a thickness of 7μm by micro-gravure coating, and then enters a coagulation bath (the coagulation bath is a solution of water and DMAC), the coagulation bath concentration is 65%, and the temperature is 40°C. After coming out of the coagulation bath, it is washed with water at 55°C, and then the diaphragm is dried at a drying temperature of 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5μm on both sides is obtained.
[0080] S2. Preparation of composite coated diaphragm: (1) Take a certain amount of isopropanol, add tetrabutyl titanate and phosphoric acid, the mass ratio of tetrabutyl titanate to phosphoric acid is 1:3, and stir at 10°C and 800 rpm for 3 h to obtain a mixed solution A.
[0081] (2) Mix isopropanol and water evenly, slowly add them into mixed solution A, and stir at 10°C and 1500 rpm for 4 h to obtain TiO2 sol; The mass ratio of isopropanol to tetrabutyl titanate in the TiO2 sol system is 5:1, and the mass ratio of water to tetrabutyl titanate is 3:3. The mass ratio of isopropanol in step (1) to isopropanol in step (2) is 1.8:1.
[0082] (3) Add polyacrylonitrile to the TiO2 sol and stir at 30°C and 1000 rpm for 30 min to obtain a TiO2 treatment solution, in which the mass proportion of polyacrylonitrile in the TiO2 treatment solution is 10%.
[0083] The aramid coated diaphragm intermediate obtained in step S1 was immersed in the TiO2 treatment solution at a speed of 80 m / min, then placed in an oven for drying at 60° C., immersed in the TiO2 treatment solution again after drying, and dried at 60° C., and repeated for 5 times in total to obtain a composite coated diaphragm.
[0084] Comparative Example 1 The difference between this comparative example 1 and the example 1 is that the TiO2 treatment solution is not used for treatment, and the aramid coated diaphragm intermediate coated with the cross-linked aramid polymer solution is directly used as the final product.
[0085] The specific method is as follows: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0086] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were mixed in a mass ratio of 89:5:6 to prepare an aramid polymer slurry, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at a drying temperature of 70°C. After winding, an aramid coated diaphragm with a coating thickness of 1.5μm on both sides was obtained.
[0087] Comparative Example 2 In this comparative example 2, aramid polymer solution and TiO2 treatment solution are not used for coating treatment, but ceramic slurry is directly coated on the surface of the base film to obtain a ceramic coated diaphragm.
[0088] The specific preparation method is as follows: 80 parts of aluminum oxide, 15 parts of poly (meth) acrylate emulsion with a solid content of 50% and 120 parts of deionized water were mixed, stirred at 30°C and 1200 rpm for 1 hour, and then 100 parts of a thickener (a CMC aqueous solution with a mass concentration of 2%) and 0.5 parts of polyethylene glycol ether were added, and stirred at 30°C and 1000 rpm for 1.5 hours to obtain a ceramic slurry; The ceramic slurry was coated on a polyethylene diaphragm with a thickness of 7 μm by micro-gravure coating, and a ceramic coated diaphragm was obtained after drying.
[0089] Comparative Example 3 In this comparative example 3, no TiO2 treatment solution is used for treatment. The aramid coated diaphragm intermediate is coated with composite oxide particles on its surface by conventional roller coating to obtain an aramid-ceramic composite coated diaphragm.
[0090] The specific preparation method is as follows: 10 kg of meta-aramid polymer stock solution was dissolved in 30 kg of DMAC. After complete dissolution, the temperature was maintained at 30° C., stirring was continued, and 0.2 kg of MDI was slowly added. The treatment time was 10 min to obtain a cross-linked aramid polymer solution.
[0091] The cross-linked aramid polymer solution, PEG (molecular weight 800), and lithium chloride were prepared into a coating slurry at a mass ratio of 89:5:6, and then the aramid polymer slurry was evenly coated on a polyethylene diaphragm with a thickness of 7μm by micro-gravure coating, and then entered a coagulation bath (the coagulation bath was a solution of water and DMAC), the coagulation bath concentration was 45%, and the temperature was 25°C. After coming out of the coagulation bath, it was washed with water at 55°C, and then the diaphragm was dried at a drying temperature of 70°C. After winding, an aramid coated diaphragm intermediate with a coating thickness of 1.5μm on both sides was obtained.
[0092] 80 parts of aluminum oxide, 15 parts of poly (meth) acrylate emulsion with a solid content of 50% and 120 parts of deionized water were mixed, stirred at 30°C and 1200 rpm for 1 hour, then 100 parts of a thickener (a CMC aqueous solution with a mass concentration of 2%) and 0.5 parts of polyethylene glycol ether were added, and stirred at 30°C and 1000 rpm for 1.5 hours to obtain a ceramic slurry; The ceramic slurry was coated on the aramid coated diaphragm intermediate by micro-gravure coating, and the aramid-ceramic coated diaphragm was obtained after drying, and the single-side thickness of the ceramic layer was 1.5 μm.
[0093] Comparative Example 4 The composite coated diaphragm was prepared by the same method as in Example 1, except that the concentration of the coagulation bath in step S1 was reduced, and the concentration of the coagulation bath in this comparative example 4 was 10%. The other process conditions were the same as in Example 1.
[0094] Comparative Example 5 The composite coated diaphragm was prepared by the same method as in Example 1, except that the concentration of the coagulation bath in step S1 was increased, and the concentration of the coagulation bath in this comparative example 5 was 80%. The other process conditions were the same as in Example 1.
[0095] Comparative Example 6 The composite coated diaphragm was prepared by the same method as in Example 1, except that the amount of the aqueous adhesive added in step S2 was reduced, and the mass proportion of the aqueous adhesive poly (meth) acrylate in the TiO2 treatment solution in this comparative example 6 was 0.5%.
[0096] Comparative Example 7 The composite coated diaphragm was prepared by the same method as in Example 1, except that the amount of the aqueous adhesive added in step S2 was increased, and the mass proportion of the aqueous adhesive poly (meth) acrylate in the TiO2 treatment solution in this comparative example 7 was 12%.
[0097] Comparative Example 8 The composite coated diaphragm was prepared by the same method as in Example 1, except that the number of times the aramid coated diaphragm intermediate was immersed in the TiO2 treatment solution was reduced. In this comparative example 8, the aramid coated diaphragm intermediate was immersed in the TiO2 treatment solution only once. The other process conditions were the same as in Example 1.
[0098] Comparative Example 9 The composite coated diaphragm was prepared by the same method as in Example 1, except that the number of times the aramid coated diaphragm intermediate was immersed in the TiO2 treatment solution was increased. In this comparative example 9, the number of times the aramid coated diaphragm intermediate was immersed in the TiO2 treatment solution was repeated 10 times. Other process conditions were the same as in Example 1.
[0099] The coated diaphragms obtained in the above examples and comparative examples were tested for thickness, air permeability, thermal shrinkage and film rupture temperature, and the test results are shown in Table 1. The thickness, air permeability, puncture strength and thermal shrinkage were tested according to the method specified in GB / T36363-2018, the film rupture temperature was tested according to the method specified in GB / T 36800.1-2018, and the moisture content was tested according to the method specified in T / SGX 002-2018.
[0100] Table 1 Performance data of the diaphragm of the embodiment and the comparative example
[0101] Note: “-” indicates that measurement is not possible under this condition; MD stands for longitudinal direction and TD stands for transverse direction.
[0102] The coated diaphragms obtained in Example 1 of the present invention and Comparative Examples 1 and 2 are assembled into soft-pack batteries, wherein the positive electrode is made of NCM811 material, the negative electrode is made of graphite material, and the electrolyte is lithium hexafluorophosphate, model: LBED8-240421. Specifically, the batteries are assembled by using a Kejing semi-automatic laminating machine through the steps of lamination, hot pressing, tab welding, top and side sealing, liquid injection, formation, and final sealing.
[0103] The assembled batteries were tested for ionic conductivity, room temperature charge and discharge rate, high temperature discharge rate and battery heating experimental performance, and the test results are shown in Table 2. The ionic conductivity was tested according to the method specified in NB / T 10827-2021, the room temperature rate discharge, room temperature rate charge and high temperature discharge rate were tested according to the method specified in GB / T 31486-2015, and the battery heating experiment was tested according to the method specified in GB / T 31485-2015.
[0104] Table 2 Performance test data of the membrane assembled battery of the embodiment and the comparative example
[0105] It can be seen from the data in Tables 1 and 2 above that Examples 1-7 are composite coated diaphragms prepared by the preparation method of the present invention, and their heat shrinkage performance, air permeability, puncture strength, film breaking temperature and moisture content can all be improved. Moreover, after assembling the battery, the electrochemical and safety performance of the composite coated diaphragm (Example 1) of the present invention are evaluated to be improved, wherein the 130°C heating experiment test, the embodiment and the comparative example can pass the test. Further increasing the test conditions to the 160°C heating test, Example 1 can pass, and Comparative Examples 1 and 2 cannot pass. The cross-linked aramid polymer and TiO2 treatment liquid layered treatment composite process provided by the present invention, on the one hand, the aramid coating maintains the original coating structure, ensuring the film breaking temperature of the product; on the other hand, the TiO2 particles are more evenly distributed on the coating surface, providing better heat shrinkage performance, and further improving the film breaking temperature of the product, so the battery safety test pass rate is higher. In addition, the process route of immersion treatment makes the TiO2 coating relatively lower in stacking density, providing more channels for lithium ions in the battery, and higher in ionic conductivity.
[0106] The surface morphology of the composite coated diaphragm prepared in Example 1 is as follows Figure 3 As shown, from Figure 3 It can be seen that the TiO2 particles prepared using this process route are more evenly distributed and the coating is more evenly stacked, thereby providing better heat shrinkage performance. Figure 4 As shown by Figure 4 It can be seen that the composite coated diaphragm has a higher membrane rupture temperature.
[0107] From the data comparison between Comparative Example 1 and Examples 1-2, it can be seen that if the diaphragm is not treated with TiO2 treatment solution, the heat shrinkage performance, puncture strength, and membrane rupture temperature of the diaphragm will all decrease, and the water content will increase. The performance of the assembled battery will also be significantly reduced. Therefore, the diaphragm obtained by co-treatment with the cross-linked aramid polymer solution and the TiO2 treatment solution has more excellent performance.
[0108] From the comparison of the data of Comparative Examples 2-3 and Example 1, it can be seen that compared with the conventional ceramic coating method, the inorganic coating is introduced on the aramid coating by layering treatment with TiO2 treatment liquid, and the diaphragm has a thinner thickness, higher puncture strength, heat shrinkage performance and film rupture temperature.
[0109] From the comparison of the data of Comparative Example 4 and Example 1, it can be seen that if the concentration of the coagulation bath is reduced, the pore structure of the aramid coating deteriorates, thereby reducing the air permeability of the product; at the same time, the film-forming property of the aramid coating deteriorates, the coating is easy to fall off, and the film breaking temperature of the product is significantly reduced.
[0110] From the data comparison of Comparative Example 5 and Example 1, it can be seen that if the concentration of the coagulation bath is increased, the film formation rate will be too fast, the pore structure of the aramid coating will be too large, the coating will be uneven, the puncture strength and film breaking temperature of the product will both decrease, and the water content will also increase. Therefore, the concentration of the coagulation bath defined by the present invention is more conducive to obtaining a composite coated diaphragm with excellent performance.
[0111] From the comparison of the data of Comparative Example 6 and Example 1, it can be seen that if the amount of aqueous adhesive added in step S2 is reduced, the adhesion force of the TiO2 particles on the surface of the diaphragm is too low, the particles cannot adhere to the surface of the diaphragm normally, and the coating is uneven, resulting in reduced puncture strength and heat shrinkage performance of the product.
[0112] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that if the amount of water-based adhesive added in step S2 is increased, the adhesive blocks the surface of the diaphragm, the air permeability is abnormal, and the water content is significantly increased. Therefore, the use of the amount of adhesive defined in the present invention is more conducive to obtaining a composite coated diaphragm with excellent performance.
[0113] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that if the number of times the aramid coated diaphragm intermediate is immersed in the TiO2 treatment solution is reduced, TiO2 cannot evenly cover the surface of the diaphragm intermediate, the coating is thinner, resulting in poor puncture strength and heat shrinkage performance of the product.
[0114] From the comparison of the data of Comparative Example 9 and Example 1, it can be seen that if the number of times the aramid coated diaphragm intermediate is immersed in the TiO2 treatment solution is increased, the inorganic particle coating is thicker. Although the heat shrinkage performance of the product is improved, the total thickness of the product is thicker and the air permeability is significantly deteriorated, affecting the normal assembly of the battery.
[0115] The cross-linked aramid polymer solution material used in the preparation method of the present invention has better heat resistance and higher strength. It is prepared into an aramid slurry and coated on the surface of the substrate by a phase inversion method to obtain an aramid diaphragm intermediate, and then a TiO2 sol is prepared in advance by a sol-gel method, and then an appropriate amount of an aqueous adhesive is mixed to obtain a treatment liquid. The aramid diaphragm intermediate is graded and treated with a TiO2 treatment liquid to compound TiO2 particles on its surface, further improving the heat resistance and puncture strength to obtain a composite coated diaphragm. The composite coated diaphragm of the present invention has higher heat resistance, film rupture temperature, puncture strength and low water absorption; in addition, the good coating pore structure of the aramid polymer after film formation and the unique chemical structure of the amide bond make the manufactured product have better liquid retention performance, and better electrochemical and safety performance after assembling the battery.
[0116] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0117] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a composite coated diaphragm for a lithium ion battery, characterized in that: The preparation method is: S1. Preparation of aramid coated diaphragm intermediate: Aramid polymer slurry is coated on the base film, and subjected to coagulation bath molding and drying treatment to obtain an aramid coated diaphragm intermediate; the aramid polymer slurry comprises a cross-linked aramid polymer solution, a porogen and a cosolvent; The cross-linked aramid polymer solution is prepared by cross-linking a meta-aramid polymer solution and an isocyanate inducing agent, and the weight average molecular weight of the cross-linked aramid polymer in the cross-linked aramid polymer solution is 15-30W; S2. Preparation of composite coated diaphragm: A TiO2 treatment liquid is coated on the surface of the aramid coated diaphragm intermediate, and finally a drying treatment is performed to obtain a composite coated diaphragm; the TiO2 treatment liquid includes a TiO2 sol and an aqueous adhesive.
2. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: The cross-linked structure polymer in the cross-linked structure aramid polymer solution is selected from the following chemical formula: 、 ; R is selected from any one of the following structures: ; 0≤n≤150, 80≤x≤150, 80≤m≤150.
3. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: The porogen is any one of polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone; The co-solvent is any one of calcium chloride and lithium chloride; The isocyanate inducer is at least one of 2,4- / 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, naphthalene 1,5-diisocyanate, p-phenylene diisocyanate, and triphenylmethane triisocyanate.
4. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: In step S1, the mass ratio of the cross-linked aramid polymer solution to the porogen and the cosolvent is (80-89): (5-8): (6-12); The solid content of the cross-linked aramid polymer solution is 5%-20%.
5. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: In step S1, the coagulation bath is a DMAC aqueous solution with a mass concentration of 20-65%; the coagulation bath temperature is 10-40°C.
6. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: In step S2, the preparation method of TiO2 sol is: (1) Add tetrabutyl titanate and acid to alcohol and stir and mix, control the temperature to 10-45° C., the stirring speed to 300-800 rpm, and the stirring time to 1-3 h to obtain a mixed solution A; (2) After the alcohol and water are evenly mixed, slowly add them into the mixed solution A and stir to mix. Control the temperature to 10-45°C, the stirring speed to 500-1500 rpm, and the stirring time to 2-4 hours to obtain TiO2 sol.
7. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 6, characterized in that: The mass ratio of tetrabutyl titanate to acid is 1:(0.5-3); The mass ratio of the total mass of the alcohol in step (1) and step (2) to the mass ratio of the tetrabutyl titanate is (2-5):1; The mass ratio of water to tetrabutyl titanate is (0.5-3):3; The mass ratio of the alcohol in step (1) to the alcohol in step (2) is (1.8-2.2): 1; The alcohol is any one of methanol, ethanol, isopropanol and n-butanol; The acid is any one of acetic acid, nitric acid and phosphoric acid.
8. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: The water-based adhesive is at least one of polypropylene resin, polyacrylic acid, polyvinyl alcohol, polyacrylonitrile, and poly(meth)acrylate; The mass proportion of the aqueous adhesive in the TiO2 treatment solution is 1-10%.
9. The method for preparing a composite coated diaphragm for a lithium ion battery according to claim 1, characterized in that: In step S2, the method for coating the TiO2 treatment liquid on the surface of the aramid coated diaphragm intermediate is: immersing the aramid coated diaphragm intermediate in the TiO2 treatment liquid for multiple times, controlling the immersion penetration speed to 20-80m / min, the immersion penetration number to 2-5 times, and finally drying and processing to obtain a composite coated diaphragm.
10. A composite coated diaphragm for lithium ion batteries, characterized in that: The composite coated diaphragm is prepared according to the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Aramid fiber polymer coated lithium ion battery membrane and preparation method thereof
CN104979515A
Aramid coated lithium ion battery diaphragm and preparation method thereof
CN104993089A
Non-woven fabric based multi-layer composite diaphragm for lithium ion battery and preparation method of multi-layer composite diaphragm
CN105470435A
Aromatic polyamide slurry and preparation method thereof, and porous diaphragm and preparation method thereof
CN109950456A
Modified aramid polymer, aramid membrane casting solution, lithium battery diaphragm, preparation methods and lithium battery
CN112538162A
Cited By
Ultrathin coating composite diaphragm for lithium metal battery as well as preparation method and application of ultrathin coating composite diaphragm
CN120237376A
Ultra-thin coating composite diaphragm for lithium metal battery and preparation method and application thereof
CN120237376B
Low-closed-cell high-temperature-resistant lithium battery diaphragm as well as preparation method and preparation device thereof
CN121709851A
In-situ polymerized aramid-based polymer electrolyte, and preparation method and application thereof
CN121748518A
Aramid fiber coated diaphragm as well as preparation method and application thereof
CN122436664A
